Maintenance Counseling and Psychotherapy: A Continuous Support for Emotional Health - Sava, Nicu-Ionel; Popa, Brigitte; Dolea, Mihaela (New Trends in Psychology, 2025)
The present paper examines the relevance of counseling and maintenance psychotherapy as a sustained framework for protecting and enhancing emotional health. Rather than being viewed as a mere post-treatment follow-up, maintenance interventions are conceptualized here as an integral part of the therapeutic process, aimed at consolidating psychological change and supporting long-term adaptation. Through a critical synthesis of current literature and clinical perspectives, the article highlights how regular counseling sessions contribute to preventing relapse, improving emotional regulation, and strengthening clients’ ability to cope with life stressors. Particular attention is given to the importance of tailoring maintenance plans to individual needs, balancing session frequency, psychoeducational components, and therapeutic goals. The discussion also explores the ethical and systemic implications of integrating maintenance psychotherapy into standard mental health services. Overall, the paper argues for a broader recognition of maintenance counseling as a preventive and developmental tool, essential not only for sustaining treatment gains but also for promoting resilience and overall well-being.